Characterization and optimization of indoor environmental quality on grey oyster (Pleurotus pulmonarius) mushroom cultivation - Islam, Md. Tariqul (School of Bioprocess Engineering, 2017)
Generally, this research study is aiming to characterize the indoor condition and investigate the performance of indoor cultivation of grey oyster (P. pulmonarius) mushroom.The specific objectives of this research study are to characterize the temperature and humidity for the indoor environment of the building during mushroom cultivation; to evaluate the mushrooms morphology, moisture content, and yield from different environmental cultivation methods; to optimize the humidifying procedure at optimum humidity and favorable temperature with maximum yield, morphology and moisture contents compared by outdoor cultivation; to analyze mushrooms morphology, moisture contents and biochemical contents from changes of temperature and humidity.